Prehistoric Pinkerton - Kellogg, Steven (New York : Dial Books for Young Readers, 1987)
Pinkerton's natural canine urge to chew on things while teething coincides with a chaotic visit to the museum's collection of dinosaur bones.
Mode of access: Internet.
SPEC WALP: In the Lee Walp Family Juvenile Book Collection, Gift of the Lee Walp Family. First printing. In dust jacket. Manuscript notes by Lee Walp. Lee Walp's clippings, notes, etc. laid in.
Keywords: Fossils -- Juvenile fiction; Museums -- Juvenile fiction; Dogs -- Juvenile fiction